Governance, risk management, compliance on preventing potential fraud in Indonesian state-owned port service industry - Sitompul, Yan Berhen Pangondian (Indonesian Journal of Multidisciplinary Science, 2024)
This study aims to determine the effect of corporate governance, risk management, and compliance with applicable regulations on the prevention of potential fraud based on the Pentagon Fraud concept. For companies engaged in the Port Service Industry, the results of this research are expected to contribute to the implementation of governance, risk management, and compliance with the prevention of potential fraud in the state-owned port service industry in Indonesia. The respondents used in this study were employees of companies engaged in Port Services. Data were collected using interviews, observations, and questionnaires. Descriptive analysis, data quality analysis, and structural model analysis are used to test hypotheses. In this study, it is known that Governance has a non-significant influence on the prevention of potential fraud compared to risk management and compliance which has a significant influence on the prevention of potential fraud.